Investigation of cavitation erosion of high vanadium alloyed powder-metallurgy tool steel - Lek, Yung Zhen (Nanyang Technological University, 2020)
Cavitation erosion is a phenomenon that occurs when the pressure of the liquid drops below its vapour pressure. It forms bubbles and cavities; these cavities explode when the pressure returns to above vapour pressure sending shock waves. When the shock waves interact with the material over an extended period, erosion occurs. Cavitation erosion mainly affects pump impellers, turbines, and pipes. To prolong the life of the part subjected to cavitation erosion, there are some techniques adopted such as surface enhancement processes, designing the part to produce less cavitation or using a material that has better resistance. ASP 2053 is a high vanadium alloyed powder-metallurgy tool steel known for its high wear resistance and fatigue life that is mainly used in tool steel applications. Its good characteristics may contribute to high resistance to cavitation erosion. Although ASP 2053 is used in the industry, however no studies on its cavitation erosion resistance and its erosion mechanism have been reported. Thus, this investigation could provide more information. In this investigation, ASP 2053 was studied to understand its cavitation erosion resistance and its erosion mechanism. The specimens were tested using the ASTM G32-16 set up where an ultrasonic transducer was used to create cavitation impingement on the surface of the specimen. The mass loss was recorded at an hourly interval. Surface damage was observed under the scanning electron microscope. 2D XRD was used to measure the compressive residual stresses induced in the material before and after cavitation erosion. Results showed that ASP 2053 resistance was greatly increased after heat-treatment processing and the erosion for ASP 2053 occurs on the weaker phase boundaries followed by dislodging of the carbides. Even though retained austenite was thought to improve cavitation erosion resistance due to phase transformation, however the low transformability of ASP 2053 suggests that the retained austenite levels in the material does not seem to be a factor in its cavitation erosion resistance. Instead, ASP 2053’s matrix cohesion and finely dispersed carbides are the contributing factors for its erosion resistance.